GUIDANCE ON MARRIAGE AND ISLAMIC FAMILY LAW: STRENGTHENING FAMILY RESILIENCE IN FACING THE DYNAMICS AND COMPLEXITIES OF CONTEMPORARY FAMILIES - Febrianti, Lora; Sulfinadia, Hamda; Ahmad Nadzri, Amirulhakim Bin (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose - This study aims to analyze the implementation of marriage guidance in the Religious Affairs Office (KUA) of the East Padang Sub-district and identify the inhibiting factors. This study also examines the relevance of marriage guidance from the perspective of contemporary family law, especially in improving family resilience by understanding the rights and obligations of husbands and wives. Methods: This research is qualitative field research. Data were collected through interviews with the Religious Affairs Office Staff, prospective brides, and other resources involved in marriage guidance. The descriptive analysis method was used to understand the implementation patterns and constraints of this guidance program. Findings - The results showed that marriage guidance at the Religious Affairs Office (KUA) of East Padang Sub-district was conducted one week before the marriage contract. The material presented includes household development, responsibilities and obligations of husbands and wives, educating children, and worship in the household. The delivery of the material involved the KUA, the Health Office, BKKBN, religious counselors, and traditional leaders using lectures, questions and answers, and discussions. The main inhibiting factors were the discipline of the bride and groom and a lack of awareness of the importance of marriage guidance. Contributions/Limitations - This study contributes to understanding the role of marriage guidance in building family resilience when facing challenges in the contemporary era. The findings can serve as a reference for policymakers seeking to improve the effectiveness of marriage guidance in Indonesia.